Application of SWOT in Improving Sustainable Entrepreneurship (K’S Eco Bag Case Study) - Amalia, Dianita Nur; Hendayana, Yayan (Dinasti International Journal of Management Science, 2024)
One of the global problems currently being faced is environmental contamination or damage. Plastic is one of the biggest contributors to waste. For this reason, K's Eco Bag is here as a solution to reduce the amount of plastic waste that accumulates in the environment by recycling plastic into bags. This research aims to analyze the application of SWOT in increasing sustainable entrepreneurship in the K's Eco Bag business. The results of this research are that the K's Eco Bag business has implemented a sustainable concept, by turning plastic waste into bags that have a high selling value and collaborating with the Fairatmos organization to reduce carbon emissions in the environment. SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) used in developing sustainable entrepreneurship for K's Eco Bag recycled plastic bags can help this business maximize existing potential and opportunities while overcoming weaknesses and threats that may arise. so that it can compete in the fashion industry market. With this approach, businesses can increase profitability and long-term sustainability. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with qualitative method sourced from previous research literature from researchers.